Hubungan Usia dan Jenis Kelamin dengan TB MDR - Marlin Sutrisna; Elsi Rahmadani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Pulmonary tuberculosis is a serious health problem with a fairly high prevalence, including MDR TB. Many factors can affect MDR TB. The purpose of this study was to determine the age and sex with MDR TB. The method in this study is quantitative, using descriptive analytic observational with a cross sectional approach. This research was conducted in the Jasmine Room of Dr. M Yunus Hospital. The sample in the study amounted to 35 respondents who were selected according to the inclusion and exclusion criteria. This study used the chi-square statistical test. The results of this study indicate that most of the respondents 22 (62.9%) suffer from MDR TB, most of the respondents are 17 people (48.6%) in 46 years, more than most of the respondents 20 people (57.1%) are male. - man. The results of the chi-suare test showed that there was a relationship between age and sex with the incidence of MDR TB, with p value <0.05. The conclusion in this study is that age and gender are one of the factors associated with the incidence of MDR TB in the Matahari Room of RSUD dr. M. Yunus Bengkulu.